2010
DOI: 10.1093/ndtplus/sfq063
|View full text |Cite
|
Sign up to set email alerts
|

Long-term graft function changes in kidney transplant recipients

Abstract: Background. Monitoring changes in glomerular filtration rate (GFR) is the recommended method for assessing the progression of kidney disease. The aim of this study was to assess the decline of graft function defined by the annualized change in GFR and the factors which affect it.Methods. Four thousand four hundred and eighty-eight patients, transplanted during the years 1990, 1994, 1998 and 2002 in 34 centres in Spain with allograft survival of at least 1 year, were included in the study. GFR was estimated usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 24 publications
4
44
1
1
Order By: Relevance
“…Grinyo et al analyzed the results of 872 renal transplant recipients with functioning graft at least 2 years after transplantation and found chronic allograft nephropathy (according to laboratory criteria: creatinine level >2 mg/dL and eGFR <50 mL/min) in 55.5% of patients after approximately 8 years from the time of renal transplantation [8]. The study of Marcén et al found CAD in 62.5% of patients 12 months after transplantation based on eGFR <59 mL/min [9]. In our study, diagnosis of CAD was based on increased of serum creatinine >2 m/dL, decreasing eGFR <50 mL/min, proteinuria, and poor control of arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Grinyo et al analyzed the results of 872 renal transplant recipients with functioning graft at least 2 years after transplantation and found chronic allograft nephropathy (according to laboratory criteria: creatinine level >2 mg/dL and eGFR <50 mL/min) in 55.5% of patients after approximately 8 years from the time of renal transplantation [8]. The study of Marcén et al found CAD in 62.5% of patients 12 months after transplantation based on eGFR <59 mL/min [9]. In our study, diagnosis of CAD was based on increased of serum creatinine >2 m/dL, decreasing eGFR <50 mL/min, proteinuria, and poor control of arterial hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…На большом клиническом материале доказано, что некоторые параметры могут служить прогнос-тическими критериями долгосрочной выживае-мости трансплантата [5][6][7][8][9][10][11][12][13], причем площадь под ROC-кривой достигает 0,86, что указывает на до-статочную прогностическую ценность этих пока-зателей. Большинство авторов сходятся во мнении, что в качестве таких критериев могут быть исполь-зованы такие простые, и что важно -неинвазивные методы, как измерение СКФ, концентрации креати-нина и суточной протеинурии.…”
Section: Discussionunclassified
“…With this in mind, let us put into context the creatinine measurement and kidney function after transplantation. Whether 1, 5, or 10 years after transplantation, the GFR based on serum creatinine places the majority of patients into the stage 3T CKD (41). As seen in Figure 3, kidney function is reasonably stable over time with a slight trend toward a decrease over years as indicated by the slight shift to the left (42).…”
Section: Monitoringmentioning
confidence: 90%